Heuristics and biases: The psychology of intuitive judgment - Gilovich, thomas; Griffin, Dale; Kahneman, Daniel (New York Cambridge University Press, 2002)
Judgment pervades human experience. Do I have a strong enough case to go to trial? Will the Fed change interest rates? Can I trust this person? This book examines how people answer such questions. How do people cope with the complexities of the world economy, the uncertain behavior of friends and adversaries, or their own changing tastes and personalities? When are people's judgments prone to bias, and what is responsible for their biases? This book compiles psychologists' best attempts to answer these important questions.